Fabrication of all‐cellulose nanocomposites from corn stalk. (22nd June 2020) - Bian, Hongxia; Tu, Peng; Chen, Jonathan Y
Abstract: BACKGROUND: There is a need to help farmers and industries develop value‐added composite and nanocomposite materials from agricultural residuals. Cellulose nanofibers (CNFs) were made using a TEMPO oxidation method and celluloses were prepared by acid–base method and extracting method, which were all from corn stalk, an agricultural residual. The prepared celluloses were dissolved separately in dimethylacetamide/LiCl solvent and CNFs were added at 0.0%, 0.5%, 1.5% and 3.0% to form all‐cellulose nanocomposites, and then cast into films. Morphology, structure and properties of the nanocomposite films were characterized using atomic force microscopy, field emission scanning electron microscopy, thermogravimetric analysis, X‐ray diffraction and mechanical testing. RESULTS: The all‐cellulose nanocomposite films with different cellulose matrices exhibited good optical transparency and layer structure. The all‐cellulose nanocomposite films with cellulose prepared by the extracting method (Composite E) exhibited a higher crystallinity, better thermal stability and higher mechanical strength compared to the all‐cellulose nanocomposite films with cellulose prepared by the acid–base method (Composite A). CONCLUSIONS: The crystal structure of the all‐cellulose nanocomposite films indicated the coexistence of cellulose I and cellulose II. However, in contrast to Composite A, the diffraction intensity of cellulose I in Composite E was higher than that of cellulose II. This was another reason that the mechanical properties of Composite E were superior to those of Composite A. In addition, the mechanical properties of the all‐cellulose nanocomposite films were significantly different when the addition of CNFs reached 3.0% by weight, as indicated by a multiple‐range comparison. © 2020 Society of Chemical Industry